2014
DOI: 10.1007/s40615-014-0035-1
|View full text |Cite
|
Sign up to set email alerts
|

Race Differences in Personality and Affect Between Older White and Black Patients: an Exploratory Study

Abstract: Objective There is limited research focusing on the five-factor model (FFM) of personality among diverse older adults, particularly cancer patient populations. This study aimed to examine the association of personality traits, positive and negative affect, and health in White and Black older adults receiving outpatient treatment for various cancer types. Design Data were collected from 150 patients (123 White and 27 Black patients), with a mean age of 65.38 years (SD=7.72). Participants were surveyed on person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Although there is some evidence that positive psychological factors may also differ across race/ethnicity, results have been mixed, and studies have predominantly been conducted in nonclinical (ie, pain‐free) populations. Of these, similar levels of optimism , resilience , social support , and dispositional hope have been observed across race/ethnicity, whereas other studies have found higher PA among NHBs relative to white participants . In the two studies exploring pain‐coping differences in an OA population, one found lower arthritis self‐efficacy in NHBs ; however, comparable levels of pain self‐efficacy across race/ethnicity have also been noted .…”
Section: Discussionmentioning
confidence: 85%
“…Although there is some evidence that positive psychological factors may also differ across race/ethnicity, results have been mixed, and studies have predominantly been conducted in nonclinical (ie, pain‐free) populations. Of these, similar levels of optimism , resilience , social support , and dispositional hope have been observed across race/ethnicity, whereas other studies have found higher PA among NHBs relative to white participants . In the two studies exploring pain‐coping differences in an OA population, one found lower arthritis self‐efficacy in NHBs ; however, comparable levels of pain self‐efficacy across race/ethnicity have also been noted .…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, previous research has largely focused on Caucasian older adults [9] and thus it is unclear how these traits relate to risk of dementia in more diverse populations. This is an important limitation, as relationships between personality and other health outcomes differ by race, including between white and black individuals [13,14], and there are known racial disparities in rates of dementia and other factors that influence dementia risk [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] These contextual factors are also able to change additive and multiplicative effects of risk and protective factors even when their separate effects are similar. [ 7 8 9 10 11 12 13 14 ] Race, ethnicity, gender, and their intersections modify the separate[ 15 ] and combined[ 16 ] effects of anxiety and depressive disorders on obesity,[ 15 16 17 ] cardiovascular diseases (CVDs)[ 6 17 18 19 ] and well-being. [ 7 ] The International Journal of Preventive Medicine[ 10 11 12 ] and a few other journals[ 13 14 20 21 ] are making an immense contribution to this field by publishing the results of empirical evidence suggesting how race, ethnicity, and gender operate as moderators.…”
mentioning
confidence: 99%